2014
DOI: 10.1134/s2079086414050077
|View full text |Cite
|
Sign up to set email alerts
|

Extinction of large herbivore mammals: Niche characteristics of the musk ox Ovibos moschatus and the reindeer Rangifer tarandus coexisting in isolation

Abstract: The extinction of large northern herbivores is a puzzle for many biologists. Is it caused by climate change or human activity? The survival of the weak trophic competitors promotes the "anthropogenic" hypothesis. The extant species of Pleistocene communities allow us to easily test this assumption. The rein deer and musk ox have been until now coexisting in the Arctic territory. Their island populations form a unique natural experiment for assessing the role of competition. On Wrangel Island, changes in their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 28 publications
0
4
0
1
Order By: Relevance
“…The relative influence of humans and rapid climatic warming during the Pleistocene-Holocene transition in this mass extinction has been widely debated. The extinction of large-and slow-breeding animals strongly implicates human hunting in such extinctions, although it is plausible that rapid climate changes during the same period also contributed [9][10][11]. For at least two formerly abundant Pleistocene large herbivores, the steppe bison and woolly mammoth, paleoecological evidence and bioclimatic envelope modelling suggest that human expansion into the far north probably coincided with rapid warming in the demise of such species [12,13].…”
Section: The Arctic Herbivore Species Assemblagementioning
confidence: 99%
“…The relative influence of humans and rapid climatic warming during the Pleistocene-Holocene transition in this mass extinction has been widely debated. The extinction of large-and slow-breeding animals strongly implicates human hunting in such extinctions, although it is plausible that rapid climate changes during the same period also contributed [9][10][11]. For at least two formerly abundant Pleistocene large herbivores, the steppe bison and woolly mammoth, paleoecological evidence and bioclimatic envelope modelling suggest that human expansion into the far north probably coincided with rapid warming in the demise of such species [12,13].…”
Section: The Arctic Herbivore Species Assemblagementioning
confidence: 99%
“…Specifically, we examined spatial overlap (broad scale), habitat selection (intermediate scale), and diet overlap (fine scale) between a declining migratory caribou herd and an introduced muskoxen population to determine whether they showed potential to compete for space or food. Potential for competition between caribou and muskoxen has a long history in the scientific literature (Vincent and Gunn 1981, Kutz et al 2017), with several studies across the circumpolar Arctic in systems with both endemic and introduced populations of muskoxen (Wilkinson et al 1976, Klein and Staaland 1984, Ihl and Klein 2001, Larter et al 2002, Sheremetev et al 2014). Most of these studies concluded that the potential for competition was low and that niche separation between the 2 species allowed resource partitioning and coexistence.…”
Section: Discussionmentioning
confidence: 99%
“…The finding of musk ox remains at Cowshead Cave, a location away from other sites where this species occurred, could suggest a possible southward winter migration from mainland Europe, which would involve a seasonal movement of more than 250 km. However, considering the migratory behaviour of modern musk ox populations, this possibility seems unlikely: in contrast to other ungulates such as reindeer, in which many populations perform long seasonal migrations between summer and winter ranges (Moen et al, 2006;Schmidt et al, 2016), most authors agree that musk ox is a relatively sedentary species which only makes short displacements between its winter and summer areas (Harington, 1961;Tener, 1965;Lent, 1988;Klein, 1992;Moen et al, 2006;Sheremetev et al, 2014;Schmidt et al, 2016). According to Tener (1965), these seasonal movements generally do not exceed 50 km, which is consistent with data recently obtained by GPS location of populations from NE Greenland (Schmidt et al, 2016).…”
Section: Paleobiogeographical Implicationsmentioning
confidence: 99%